Lärka – ett verktyg för träning av språkterminologi och grammatik - Tiedemann, Therese Lindström; Volodina, Elena; Jansson, Håkan (LexicoNordica, 2019)
Lärka is a corpus-based tool, which allows students to practise and learn grammatical terminology (such as parts of speech and syntactical categories) and semantics while practicing their analytical skills based on authentic material. In this study we present how this has been used at four universities. We also use our logs to try to assess the students’ metalinguistic awareness in relation to international studies, and discuss how these logs can be used in the future.